Comparison of Chemical Compounds of Essential Oils from Natural Agarwood and Inoculated Agarwood (Roselle-Based Inoculation) - N.R.M. Nasardin; M.A.M. Hanafiah; M. Zainon; M. Ibrahim; A.I.A. Rahman; Z.A. Baharudin; M.H.M. Husin; I. Mahir; A.A. Zulkefle (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
In this paper, the physical and structural properties of the natural agarwood and inoculated agarwood using Roselle-based inoculation had been discussed. The results showed that a high volume of oil obtained on day 1 by the inoculated agarwood which yielded 3ml of the agarwood oil as compared to the natural agarwood that had yielded only 2.3ml. In the chemical analysis, five major compounds were detected by FTIR which were C-O bond (aromatic alkane), C-C stretching (aromatic alkane), C-O stretching (ether) and C-H bond (aromatic ring) in both oils. Moreover, the inoculated agarwood exhibited better oil production compared to the natural agarwood.